Exploratory secondary analyses of a cognitive-behavioral intervention for knee osteoarthritis demonstrate reduction in biomarkers of adipocyte inflammation. Issue 9 (September 2016) - Huebner, J.L.; Landerman, L.R.; Somers, T.J.; Keefe, F.J.; Guilak, F.; Blumenthal, J.A.; Caldwell, D.S.; Kraus, V.B.
Summary: Objective: To investigate the effects of pain coping skills training (PCST) and a lifestyle behavioral weight management (BWM) program on inflammatory markers and biomarker associations with pain and function in the OA LIFE study. Method: Serum samples were available from a subset ( N  = 169) of the overweight or obese knee OA participants in the OA LIFE study that evaluated: PCST, BWM, combined PCST + BWM, or standard care (SC). Inflammatory markers (hsCRP, IL-1ra, IL-1β, IL-6, IL-8, TNF-α, TNFRI, TNFRII, and hyaluronic acid (HA)), and adipokines (leptin and adiponectin) were measured before and after the 24-week treatment period. Biomarkers were assessed for effects of treatment and for associations with change in weight, pain and disability (unadjusted and adjusted for age, race, sex, baseline body mass index (BMI), and baseline biomarker concentration). Results: PCST + BWM was associated with significant reductions in hsCRP ( P  = 0.0014), IL-6 ( P  = 0.0075), and leptin ( P  = 0.0001). After adjustment, there was a significant effect of PCST + BWM on changes in leptin ( b  = −0.19, P  = 0.01) and IL-6 ( b  = −0.25, P  = 0.02) relative to SC. Reductions in leptin and IL-6 were significantly correlated with reductions in weight, BMI and Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain; reductions in IL-6 were correlated with improvements in WOMAC and Arthritis Impact Measurement Scales (AIMS) physical function. By mediation analyses, weight loss was responsible for 54% of the change in IL-6 and all of the change in leptin. Conclusions: OA-related inflammatory markers were reduced by a 24-week combined PCST + BWM intervention. This suggests that the inflammatory state can be successfully modified in the context of a readily instituted clinical intervention with a positive clinical outcome.